Hubungan Kompetensi Pedagogik Dan Literasi Guru Dengan Kinerja Guru Madrasah Ibtidaiyah Kota Bekasi - Angkling Maulana Haz; Baharuddin; Ibnu Muthi (Jurnal Pendidikan dan Pembelajaran, 2022)
Teachers have a very strategic function and role in the development of the education sector. Therefore, it needs to be developed as a dignified profession. Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers Article 4 confirms that teachers as learning agents function to improve the quality of national education, to be able to carry out their functions properly. Teachers are required to have certain conditions, one of which is competence. Teacher competence is the ability and authority of a teacher in carrying out his obligations responsibly related to the teaching profession. This study uses associative quantitative research methods, this research method was chosen with consideration to determine whether or not there is a relationship between teacher pedagogic competence and literacy with teacher performance. This study uses two variables consisting of the dependent variable and the independent variable. The dependent variable is "Teacher Performance" while the independent variables are "Pedagogic Competence" and "Teacher Literacy". Pedagogic competence for madrasa teachers is very necessary so that there is a relationship between pedagogic competence and teacher performance itself. If the teacher masters the Pedagogic Competence, then the performance of the madrasa teacher will run according to his duties and functions as a teacher, educator, teacher, companion for students in the learning process. The research method is a scientific procedure or method to obtain data with a specific purpose, the research method is basically a scientific feature to obtain data with a specific purpose and use.